A typological anomaly in some Surma languages - Peter Unseth (LibraryPress@UF, 1987)
This paper presents evidence that at least three languages in the Surma group (and possibly also Proto-Surma) are exceptions to the proposed typological "universal" that languages with basic VSO word order do not have post-positions [Greenberg 1963:78]. There is no attempt made here to hypothesize how this came about, only to call attention to the fact that these three languages are typologically anomalous.